How keeping active pays off in the olfactory system - Monahan, Kevin (eLife Sciences Publications, Ltd, 2012)
A protein that is found in the main olfactory epithelium of mice ensures that odour-sensing neurons that are active to have longer lifespans than those that are inactive.